(untitled) (Archives of Criminology, 2012)
In interwar Poland (between 1918-39) banknotes, coins, saving books, and checks were counterfeited. Coins and banknotes were poor protected, some people have rarely dealt with them, and thereby mostly coins and banknotes were falsified. Foreign countries’ banknotes such as for example US dollars were also falsified. Forgery was done by organized crime groups with their own network of distributors who introduced forgeries into circulation. Skilful craftsmen and even manual workers moonlighted with forgery of coins and banknotes. Quick forgery of newly issued money proves the efficiency of the forgers. In addition to the methods used for centuries they invented also new ones. They showed a great invention in gaining similar or even the original paper to falsify money. Graphic designers, printers, lithographers and artists were employed in the production process. After their activities were exposed, they moved to other part of the country to continue their procedure there. The research shows that distributors where the ones most frequently caught by police. Forgers were seldom given away by the distributors who sometimes even did not each other as the criminal network consisted of several middlemen acting in conspiracy. As more and more people learned to recognize Polish money and the economic situation improved, the scale of counterfeiting of money slightly decreased. This tendency is especially visible in the last years of the Second Polish Republic, although the difficulty of verifying statistical data that show different trends in different sources should make one cautious about their credibility. Based on media reports it must be assumed with high probability that the largest size of this phenomenon took place in the early years of the Second Republic. The available data indicate different frequency of appearance of falsified money in the circulation. Most of it was probably not in Warsaw or other big cities but where people very poorely rec-ognized Polish coins and banknotes. Reports of forgeries from such areas are not most numerous. Regulation on the procedure for taking, sharing and retention of falsified currency and its implementing rules, issued in 1927 by the President of the Republic should be considered as belated. The fight against counterfeiting of money was one of the main tasks of the International Commission of the Criminal Police of which the Polish National Police was an active member. It also cooperated in this area with police forces from other European countries and even with the U.S. Federal Service of Investigation (FBI). In order to make the prosecution of money falsification more effective there was a special office and file of falsifiers and falsified money organized and maintained by the Police Headquarters. The instruments to motivate the police to prosecute counterfeiters were also introduced. Criminalist studies played an important role in the process of detection.